Analisis Persepsi Siswa Terhadap Nilai Keindonesiaan Melalui Upacara Bendera SD Muhammadiyah 2 Limboto Kabupaten Gorontalo - Selby Bolilio; Yane Hardiyanti Mahmud; Fandi H. Binggo; Thamrin A. Kum (Fakultas Pendidikan, Universitas Sultan Muhammad Syafiuddin Sambas, 2024)
This research aims to analyze students' perceptions of Indonesian values through flag ceremonies at SD Muhammadiyah 2 Limboto, Gorontalo Regency. The study employs a qualitative descriptive method with data collection procedures through observation, interviews, and documentation. In this research, inductive data analysis is conducted through data collection, analysis, presentation, and drawing conclusions. The research data sources involve primary data sources, consisting of the school principal, teachers, and students. The results of the research indicate that educators' efforts in implementing Indonesian values in students at SD Muhammadiyah 2 Limboto, Gorontalo Regency, have been well executed. This is evident in aspects such as discipline, nationalism, leadership, and camaraderie established among the students. The objectives of the flag ceremony are also achieved, where students demonstrate love for their homeland, nation, and religion. They also show a sense of responsibility and personal discipline, maintaining order in their daily lives. Additionally, students exhibit a spirit of mutual cooperation, the ability to lead and be led, and the capability to conduct ceremonies with reverence and orderliness. The implications and contributions of this research encompass various aspects that can affect multiple stakeholders. It can provide valuable input for educators and education professionals at SD Muhammadiyah 2 Limboto and other schools, allowing them to adopt proven practices to enhance students' Indonesian values. This study could serve as a foundation for curriculum development focused on shaping Indonesian values and improving the leadership role in instilling these values within the school environment. Furthermore, this research contributes to the education literature, particularly in the context of character formation among students.